Responses and adaptation by Nephotettix virescens to monogenic and pyramided rice lines with Grh-resistance genes - Vu, Quynh; Quintana, Reyuel; Fujita, Daisuke; Bernal, Carmencita C.; Yasui, Hideshi; Medina, Celia D.; Horgan, Finbarr G. (Wiley, 2014)
The green leafhopper, Nephotettix virescens (Distant) (Hemiptera: Cicadellidae), occasionally damages rice in Asia either directly, by feeding on the host phloem, or indirectly by transmitting tungro virus. We assessed the nature of resistance against the leafhopper in monogenic and pyramided near‐isogenic rice lines containing the resistance genes Grh2 and Grh4. Only the pyramided line was resistant to leafhopper damage. Leafhopper nymphs and adults had high mortality and low weight gain when feeding on the pyramided line and adults laid few eggs. In contrast, although there was some minor resistance in 45‐day‐old plants that possessed either Grh2 or Grh4 genes, the monogenic lines were generally as susceptible to the leafhopper as the recurrent parent line Taichung65 (T65). Resistance in the pyramided line was stable as the plant aged and under high nitrogen, and affected each of five Philippine leafhopper populations equally. Furthermore, in a selection study, leafhoppers failed to adapt fully to the pyramided resistant line: nymph and adult survival did improve during the first five generations of selection and attained similar levels as on T65, but egg‐laying failed to improve over 10 generations. Our preliminary results suggested that resistance was associated with physiological costs to the plants in some experiments. The results of this study demonstrate the success of pyramiding resistance genes through marker‐assisted breeding, to achieve a strong and potentially durable resistance. We discuss the utility of gene pyramiding and the development of near‐isogenic lines for leafhopper management.